Adoption of digital money (e-wallet) in the post COVID-19 era: The moderating role of low distribution charges and low transit time in impulsive buying: A developing country perspective - Wei, Qing; Xiao, Wendong; Yaqub, Rana Muhammad Shahid; Irfan, Muhammad; Murad, Muhammad; Yaqub, Muhammad Zafar (Frontiers in Environmental Science, 2023)
Online purchasing is increasing because customers are shifting to digital wallets and digital money, as these services are provided by different microfinance and other commercial banking sectors, and different online brands are working in Pakistan to support environmental sustainability. The objective of this study was to demonstrate to what extent low distribution charges and low transit time is contributing to impulsive buying when customers can use digital money in Pakistan. The study was conducted using survey research. Importantly, 650 questionnaires were distributed to the respondents with a received response rate of 40%. The study found that digital money (e-wallet) is positively associated with impulsive buying. Moreover, the moderating role of distribution charges and low transit time has been significant in impulsive buying has been significant. This study concludes that low transit time and load distribution charges must be considered by online businesses and brands working in Pakistan to ensure productivity and capture a larger market share of impulsive buying in Pakistan. Also, the current study contributes a theoretical framework to the knowledge and literature related to impulsive buying. The scope of this study is limited to the online businesses and brands that are working to provide products and services to the Pakistani people with the help of digital money and digital transactions. Significantly, this study provides significant future directions that are important to consider for upcoming studies to focus on and contribute to effectively.